Long-term study of bloom-forming cyanobacteria in a highly fluctuating vegetated floodplain lake: a morpho-functional approach - O'farrell, Ines (2015)
This study portrays the frequency and intensity of bloom-forming cyanobacteria in relation to highly changing environmental conditions in a floodplain lake from the Chaco-Pampean region and identifies the factors promoting the growth of different species along a 15-year period marked by important drought and flood periods. Phytoplankton in Laguna Grande was increasingly dominated by cyanobacteria represented by eight bloom-forming species bearing different eco-physiological traits. The bloom development showed strong inter-annual variability in correspondence with the depth of the lake that was affected by local rainfall and the ENSO regional phenomenon. The water level of the lake strongly influenced the species composition, favoring non-heterocystous filaments in deep turbid waters and nitrogen fixing in very short well lit, nitrogen-depleted water columns. Species morphology, dimensions and occurrence of akinetes in the filaments also varied in relation to water level. We suggest that the akinete pool of the sediments played a key role on the occurrence of recurrent Anabaenopsis cf. elenkinii and Sphaerospermopsis cf. aphanizonemoides blooms.